From Finitude to Transfiguration: A Theo-Phenomenological Reading of the Body in Eastern Orthodox Spirituality - Nicolae Turcan (Religions)
This article offers a theo-phenomenological investigation of the body, exploring the dialogue between contemporary phenomenology—especially its theological turn—and Eastern Orthodox spirituality as found in the Philokalia. Building on the phenomenological distinction between body and flesh and drawing on Orthodox theology’s understanding of the body–soul unity, the article analyzes the intramundanity and finitude of the human body, as well as its transfiguration through ascetic practices and divine grace. The Incarnation of Christ is examined as a central paradigm for rethinking embodiment, revealing the eschatological promise of glorified flesh. Concepts such as ipseity, self-affection, intentionality, and counter-intentionality are employed to articulate a phenomenological vision open to theological transcendence. Ultimately, this interdisciplinary approach affirms the possibility of a body transformed by grace and destined for resurrection.